Integrasi Plts pada Sistem Kelistrikan untuk Penyediaan Listrik di Desa Tanjung Kelumpang, Belitung Timur (Area Geosite Pantai Punai, Kawasan Geopark Belitung) - Suryanti, Irma; Tobing, Sheila (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
This research was carried out by developing simulation scenario for the integration of solar power plant into the existing electricity system in Tanjung Kelumpang Village (Punai Beach Area, Belitung Geopark Global Network) with an electricity load pattern at the location in the amount of 24.000 kWh/ day using HOMER software. The simulation scenario prepared is integrating solar power plant with 30% of the existing diesel power plant capacity (the diesel power plant capacity entering the system is 540 kW) and the PLN electricity network. The simulation and optimization results show that integrating solar power plant with 30% of the existing diesel power plant capacity and the PLN electricity network produces the most optimal value, with the number of Levelized Cost of Electricity (LCOE) is Rp 1.173/ kWh and Net Present Cost (NPC) is Rp 1.788/ kWh. The integration of solar power plant into the existing electricity system of Tanjung Kelumpang village can be a solution for providing clean, environmentally friendly energy at competitive rates. The development direction of Bangka Belitung Province is currently experiencing a transition from mining based economy to sustainable tourism based economy. The integration of renewable energy generation from solar power plant in geosite area is considered to be able to create multiplier effects to achieve sustainable development goals in tourism sector. A number of methods must be encouraged and accelerated to achieve this, such as policy making, providing infrastructure, increasing human resource competency, cooperation and investment pattern, as well as active community involvement in the process.